THE BIGGER WAVE OF HALLYU (한류) IN INDONESIA: GLOCALIZATION? - Mustikawati, Retno (PEOPLE: International Journal of Social Sciences, 2020)
Hallyu (한류) or Hallyu (한류) or best known today as K-Pop, extensively spreading in East Asian countries such as Mainland China and Taiwan. Through globalization, the Korean wave widening its influence on Southeast Asian countries, including Indonesia, since 1999. Twenty years on, in 2019, this cultural transformation from Korea to its neighbor countries continuously influence, and even more significant. Indeed Hallyu (한류) is a unique phenomenon in the Korean modern entertainment industry. After Korea massively succeeded in invading Indonesian entertainment with melodrama, film, and music, the term K-Beauty is now very familiar with Indonesian people. The invasion of Korean cosmetic brands, as they start to enter the culinary business as well, by opening Korean food restaurants in Indonesia. However, the regulation of the Indonesian Ulema Council (MUI) and Food and Drug Supervisory Agency (BPOM) regarding the requirement of Halal certified must be faced by Hallyu (한류) products when they enter the Indonesian market, as the biggest Muslim population in the world. This study is a library research which largerly qualitative. This article has considered the consequences of Korean wave’s influence through Globalization, that triggered the consumerism behavior which can be traced by the rational choice of young people in Indonesia. I seek to examine the influence of Hallyu (한류) in Indonesia in the context of Glocalization as the result of Globalization. It also presented a snapshot of how consumers react and make decisions regarding their purchases in this rapidly influence. The research findings defines that Hallyu (한류) has become an ethnocentric agent for South Korea, which had to deal with the regulation of halal matter in Indonesia. The conclusion of this paper offered some suggestions to help to minimize the pitfalls of Hallyu (한류) influence to Indonesia.